2019
DOI: 10.20944/preprints201909.0198.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impacts of Flowering Time and Tillering on Grain Yield of Sorghum Hybrids across Diverse Environments

Abstract: Sorghum in Australia is grown in water-limited environments of varying extent, generating substantial genotype × environment interaction (GEI). Much of the yield variation and GEI results from variations in flowering time and tillering through their effects on canopy development. The confounding effects of flowering and tillering complicate the interpretation of breeding trials. In this study, we evaluated the impacts of both flowering time (DTF) and tillering capacity (FTN) on yield of 1741 unique t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…The study of yield–trait performance landscapes demonstrated these are often complex, rugged surfaces to be explored by the breeding program, and thus create multiple opportunities to improve crop drought resistance and yield reaction-norms over multiple breeding program cycles ( Figure 5 ; Cooper et al, 2005 ; Hammer et al, 2006 ; Messina et al, 2011 ; Technow et al, 2021 ). These studies also demonstrate that multiple trait pathways can create temporal dynamics at a crop level, which are all conducive to drought resistance; stomatal conductance response to vapor pressure deficit ( Sinclair et al, 2010 ; Choudhary et al, 2014 ), xylem conductance ( Passioura, 1972 ; Richards and Passioura, 1989 ), plant size ( Borrell et al, 2014 ), and propensity to tillering ( Wang et al, 2020 ) can all lead to similar patterns of water use pre- and post-flowering. Agronomic management practices such as changing planting density can further affect the soil water dynamics in ways that amplify or dampen the impacts of any trait or trait combinations (e.g., Messina et al, 2011 , 2015 , 2021 ; Cooper et al, 2023 ).…”
Section: Beyond Ideotypes: Seeking Multiple Workable Solutions For Th...mentioning
confidence: 83%
“…The study of yield–trait performance landscapes demonstrated these are often complex, rugged surfaces to be explored by the breeding program, and thus create multiple opportunities to improve crop drought resistance and yield reaction-norms over multiple breeding program cycles ( Figure 5 ; Cooper et al, 2005 ; Hammer et al, 2006 ; Messina et al, 2011 ; Technow et al, 2021 ). These studies also demonstrate that multiple trait pathways can create temporal dynamics at a crop level, which are all conducive to drought resistance; stomatal conductance response to vapor pressure deficit ( Sinclair et al, 2010 ; Choudhary et al, 2014 ), xylem conductance ( Passioura, 1972 ; Richards and Passioura, 1989 ), plant size ( Borrell et al, 2014 ), and propensity to tillering ( Wang et al, 2020 ) can all lead to similar patterns of water use pre- and post-flowering. Agronomic management practices such as changing planting density can further affect the soil water dynamics in ways that amplify or dampen the impacts of any trait or trait combinations (e.g., Messina et al, 2011 , 2015 , 2021 ; Cooper et al, 2023 ).…”
Section: Beyond Ideotypes: Seeking Multiple Workable Solutions For Th...mentioning
confidence: 83%
“…The construction of this NAM complements the existing sorghum resources and the ongoing reference genome assemblies, pan-genomics projects, and database development which should increase the utility and accessibility for researchers worldwide ( Boyles et al 2019 ). The incorporation of photoperiod sensitive, nontemperately adapted material provides germplasm that is not confounded by the prevalence of dwarfing and photoperiod insensitive alleles ( Wang et al 2020 ). Here, we perform a quality assessment of the CP-NAM as a genomic resource and validate the population for use in genomic studies using pericarp and testa phenotypes as positive controls to map known genes affecting these phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…The results for DF differ from those obtained by Galicia-Juárez et al (2020), who reported early genotypes with a flowering range of 51 to 71 days, and late genotypes with a range of 72 to 79 days. Early cycle sorghums are tolerant of drought and high temperatures, they can also have higher yields compared to late flowering varieties (Menezes et al, 2021), because early maturing sorghums can evade the stress of a late drought through earlier grain filling, as this becomes a limitation for sorghum production worldwide (Wang et al, 2020). However, late sorghums are characterized by reaching a greater length and diameter of the stem and number of internodes, which are used to produce ethanol because of their high content of juice and sugar (Naoura et al, 2020).…”
Section: Agronomic Parametersmentioning
confidence: 99%